Community Cooperation and its Relation to Healthful School Living (Surkhet Journal, 2014)
The study is carried out to identify different types of school community cooperative programmes and to explore relation between school community co-operative programme and healthful school living. This study was based on the primary data as descriptive type of research design. Twelve secondary schools were selected as sample through census method. Headmaster, health teachers, three students, chairman of School Management committee and other three key persons of community people in each selected school, altogether 108 respondents were selected for the research work. Primary data were collected mainly by using interview schedule as research. After collecting data they were analyzed and interpreted using simple mathematical‌ corelation‌ like‌ corelation‌ of‌ coeficient‌ for‌ in ding‌relation‌ between‌ school‌ community‌ co-operation and healthful school living. A large number of the respondents had proper knowledge on School Health Programmme (SHP.) and all of the respondents agreed with need and importance of school community cooperation. Most of the schools have conducted parents day, formed and parent teacher‌ association‌‌ in‌ their‌school.‌ More‌ than‌ fifty‌ percent‌ schools‌ had‌ conducted‌ interaction‌ programme‌ seminar and workshops. Among those programmes, almost all were conducted irregularly, participation of the respondents (Chairman of school management committee and key persons of community people) were‌ not‌ satisied‌ in‌ these‌ programmes.‌ None‌ of‌ the‌ schools‌ had‌ conducted‌ immunization‌ and‌ nutrition‌ programmes by themselves. But all of the schools had helped in these programme. More than sixty percent of schools had conducted cleanliness campaign programmes in community. But these programmes were conducted irregularly. Healthful mental environment was satisfactory. School community cooperative programme and healthful school living relation (r) was found -1. There was negative high relationship between school community co-operative programme and healthful school living.